Physical activity levels, motivators and barriers to exercise among men and women aged 30 to 50 years in Rourkela, India - Mitravinda Aneesh; Nirupama Mahanta (Wolters Kluwer Medknow Publications, 2022)
Background: Literature suggests that middle age is a period with increasing sedentary behavior and health risks. Objective: We conducted the present study to assess physical activity levels of the adults aged 30-50 years and understand the motivators and barriers to regular physical activity. Materials and Methods: A cross-sectional study was conducted among 100 adults aged 30-50 years residing in Rourkela, Odisha. The physical activity levels of the adults were assessed using Bouchard's Physical Activity Record. Height, weight, and waist circumference of the participants were measured using standard procedures. A self-administered questionnaire was prepared to identify the motivators and barriers to physical activity/exercise behavior. Results: Nearly half of the participants were obese, 23.3% were overweight and 28% had a normal body mass index. Based on WC and waist-to-height ratio (WHtR), 84% and 79.3% of the participants had metabolic risk, respectively. Over half of the participants were physically inactive. Predominantly, low-intensity activities (yoga, slow walking) were performed as it was assumed to be sufficient. The main motivators of physical activity/exercise behavior were health scare, health benefits, weight loss, availability of resources at convenient time, and better looks. The chief barriers for exercise behavior were lack of motivation, weather, safety concerns, and lack of time. Conclusion: Despite over two-third of participants being overweight/obese, 90% of the physically active participants failed to meet the World Health Organization recommendations. Government, community, and individual participation are imperative to formulate interventions strategies to reduce the barriers to physical activity.